2020
DOI: 10.1073/pnas.2012156117
|View full text |Cite
|
Sign up to set email alerts
|

Speech can produce jet-like transport relevant to asymptomatic spreading of virus

Abstract: Many scientific reports document that asymptomatic and presymptomatic individuals contribute to the spread of COVID-19, probably during conversations in social interactions. Droplet emission occurs during speech, yet few studies document the flow to provide the transport mechanism. This lack of understanding prevents informed public health guidance for risk reduction and mitigation strategies, e.g., the “6-foot rule.” Here we analyze flows during breathing and speaking, including phonetic features, using order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
314
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(341 citation statements)
references
References 42 publications
25
314
1
1
Order By: Relevance
“…In addition, Holland et al reported that, similar to influenza, mumps, Haemophilus influenzae , whooping cough, and rubella, coronaviruses are transmitted by bioaerosol droplets [ 24 ]. Furthermore, Abkarian et al and Chong et al described how flows generated during speaking, singing, breathing, and laughing by asymptomatic and presymptomatic humans contribute to the spread of SARS-CoV-2 virus [ 4 , 5 ]. In addition, experiments and simulations were performed to quantify how exhaled air is transferred during talking and stressed that phonetic characteristics add complexity to the airflow dynamics, i.e., plosive sounds, such as certain words starting with the letter “P” in English, create intense vortical structures that act as “puffs” and quickly reach 1 m distances [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Holland et al reported that, similar to influenza, mumps, Haemophilus influenzae , whooping cough, and rubella, coronaviruses are transmitted by bioaerosol droplets [ 24 ]. Furthermore, Abkarian et al and Chong et al described how flows generated during speaking, singing, breathing, and laughing by asymptomatic and presymptomatic humans contribute to the spread of SARS-CoV-2 virus [ 4 , 5 ]. In addition, experiments and simulations were performed to quantify how exhaled air is transferred during talking and stressed that phonetic characteristics add complexity to the airflow dynamics, i.e., plosive sounds, such as certain words starting with the letter “P” in English, create intense vortical structures that act as “puffs” and quickly reach 1 m distances [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Abkarian et al and Chong et al described how flows generated during speaking, singing, breathing, and laughing by asymptomatic and presymptomatic humans contribute to the spread of SARS-CoV-2 virus [ 4 , 5 ]. In addition, experiments and simulations were performed to quantify how exhaled air is transferred during talking and stressed that phonetic characteristics add complexity to the airflow dynamics, i.e., plosive sounds, such as certain words starting with the letter “P” in English, create intense vortical structures that act as “puffs” and quickly reach 1 m distances [ 4 ]. Moreover, speech corresponding to a train of such puffs can make a conical, turbulent, jet-like flow and generate directed transport more than 2 m away in 30 s of conversation [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have explored this using idealised models, suggesting that the concentration of aerosols at 1.5–2 m from an infectious source is determined by the room ventilation. At a distance of m the concentration is determined by the exhaled plume and may be much higher [62] , [63] . This risk should particularly be considered in spaces with a high occupancy density where it is difficult to maintain distance, or where the nature of the activity means that it is essential to have closer contact.…”
Section: Exposure Risk In Other Indoor Spacesmentioning
confidence: 99%
“…4k and l). Particularly, this ballistic behavior of droplets is a result of enhanced jet-like transport of the expelled airflow induced by the plosive sound 46 Figure 6i shows the coughing frequency versus the average coughing intensity for all hourly measurements, clustered into four demographic groups (males with age < 55, males with age ≥ 55, females with age < 55, females with age ≥ 55). The available results suggest that females tend to cough more than males.…”
mentioning
confidence: 99%